Growth and Labelling of Cell Wall Components of the Brown Alga Ectocarpus in Microfluidic Chips - Charrier, Bénédicte; Boscq, Samuel; Nelson, Bradley J.; Läubli, Nino F. (Frontiers in Marine Science, 2021)
Polydimethylsiloxane (PDMS) chips have proven to be suitable environments for the growth of several filamentous organisms. However, depending on the specimen, the number of investigations concerning their growth and cell differentiation is limited. In this work, we monitored the developmental pattern of the brown alga Ectocarpus inside PDMS lab-on-chips. Two main methods of inoculation of the lab-on-chip were tested, i.e., via the direct injection of spores into the chamber as well as through the insertion of sporophyte filaments. The resulting growth rate, growth trajectory, cell differentiation, and cell branching were monitored and quantified for 20 days inside 25 µm or 40 µm parallel channels under standard light and temperature conditions. With growth rates of 2.8 µm·h-1, normal growth trajectories and cell differentiation, as well as branching occurring inside the microfluidic environment, the main development steps were shown to be similar to those observed in non-constrained in-vitro conditions. Additionally, the labelling of Ectocarpus cell wall polysaccharides using calcofluor for cellulose detection and immunolocalisation with monoclonal antibodies for alginates showed the expected patterns when compared to open space growth evaluated with either epifluorescence or confocal microscopy. Overall, this article describes the experimental conditions for observing and studying the basic unaltered processes of brown algal growth using microfluidic technology which provides the basis for future biochemical and biological researches.